Mitochondrial Antioxidant SkQ1 Has a Beneficial Effect in Experimental Diabetes as Based on the Analysis of Expression of microRNAs and mRNAs for the Oxidative Metabolism Regulators - Yuliya Dvoretskaya; Victor Glanz; Mariya Gryaznova; Mikhail Syromyatnikov; Vasily Popov (MDPI AG, 2021)
Diabetes mellitus and related complications are among the most important problems of the world-leading healthcare systems. Despite their priority, molecular and genetic aspects of diabetes pathogenesis are poorly understood; however, the involvement of oxidative stress in this process is undoubted. Rats with experimental diabetes induced by the intraperitoneal injection of alloxan were subjected to the antioxidant pre-therapy with a series of mitochondria-targeted 10-(6'-plastoquinonyl)decyltriphenylphosphonium (SkQ1) injections and analyzed for the expression of mRNAs and microRNAs by real-time quantitative polymerase chain reaction to identify potential predictors of diabetes. Animals that received SkQ1 before diabetes induction demonstrated lower blood glucose levels compared to the diabetic animals not subjected to the therapy. SkQ1 caused changes in the mRNA levels of genes involved in the cellular defense against free radicals, which indicates a beneficial effect of the pre-therapy. Moreover, similar changes were observed on the epigenetic level, as the microRNA expression patterns not only proved the SkQ1 efficacy but also correlated with the expression levels of their mRNA targets. Oxidative stress and macromolecule damage by free radicals are determining factors in diabetes, which suggests that strategies aimed at restoring the antioxidant status of the cell can be beneficial. Mitochondria-targeted antioxidant SkQ1 demonstrates positive effects on several levels, from the normalization of the blood glucose content to genetic and epigenetic changes. Our results can serve as a basis for the development of novel therapeutic and diagnostic strategies.